OPEN STOMATA 1 activates SLAC1 anion channel primarily through CPK15 in ABA-induced stomatal closure in Arabidopsis - Xin Shen; Kaili Yin; Zhiyu Wang; Zhiwei Zhang; Mengqing Liu; Sheng Luo; Shaowu Xue; Honghong Hu (Proceedings of the National Academy of Sciences, 2025)
The Ca 2+ -independent OST1 and Ca 2+ -dependent protein kinases CPKs both activate the anion channel SLAC1 during ABA-induced stomatal closure pathway. However, the mechanism by which OST1 regulates SLAC1 activation and its relationship with CPKs remain unclear. Here, we identify that OST1 primarily activates SLAC1 in this process through CPK15. Mutation of CPK15 significantly impairs ABA-induced stomatal closure and increases drought sensitivity. OST1 interacts with CPK15 and phosphorylates it at T103, which is essential for ABA-induced stomatal closure. Moreover, CPK15 can phosphorylate eight sites in the N terminus of SLAC1 to activate its anion currents in oocytes. Expression of SLAC1 8D (a phosphomimetic form) in oocytes constitutively activates anion channel activity and effectively restores the impaired ABA-induced stomatal closure of cpk15-1 but not by SLAC1 8A (a phospho-dead form). Furthermore, activated CPK15 by OST1 and Ca 2+ enhances its activity toward SLAC1, and mutations of both OST1 and CPK15 have additive effect on ABA-induced stomatal closure, suggesting that CPK15 activates SLAC1 through both direct and indirect mechanisms. These findings demonstrate the key role of CPK15 in ABA-induced stomatal closure, revealing a connection between OST1 and CPKs in both Ca 2+ -independent and Ca 2+ -dependent pathways in ABA-induced stomatal closure.